PENGARUH MODEL BELAJAR PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INSTALASI TENAGA LISTRIK SISWA XI DI SMK NEGERI 1 PERCUT SEI TUAN TA.2019/2020 - Arif Sahron; Baharuddin . (JEVTE: Journal of Electrical Vocational Teacher Education, 2021)
Abstract This study aims to determine the effect of the project based learning (PJBL) learning model on the learning outcomes of electric power installation in class XI TITL at SMK. This study used a quasi-experimental method with a Posttest Only Control Group Design model. The number of research subjects was 62 students, consisting of 32 students of class XI TITL 1 as the experimental class and 32 students of class XI TITL 2 as the control class. The data collection technique used was a multiple choice written test which had been tested for validity, reliability, difficulty level, and differentiation power. The results showed that the learning outcomes of the project based learning model showed that the students' average score in the experimental class was 77.33 while the control class was 71.16. From the results of the calculation of the hypothesis test, it is obtained tcount 3.261 and ttable is 1.670, then tcount> ttable or 3.261> 1.670, so it can be concluded that the alternative hypothesis (Ha) in this study is accepted while rejecting the null hypothesis (Ho) in other words the learning outcomes of class XI students. Electrical Power Installation Techniques on the competence of understanding the installation and measurement of earth systems with a project based learning (PPA) learning model are higher than student learning outcomes using conventional learning models..Key Words: Project based learning model, learning outcomes AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran project based learning (PJBL) terhadap hasil belajar instalasi tenaga listrik kelas XI TITL di SMK. Penelitian ini menggunakan metode quasi eksperimen dengan model Posttes Only Control Group Design. Jumlah subjek penelitian 62 orang peserta didik, yang terdiri dari 32 peserta didik kelas XI TITL 1 sebagai kelas eksperimen dan 32 peserta didik kelas XI TITL 2 sebagai kelas kontrol. Teknik pengumpulan data yang digunakan adalah tes tertulis berbentuk pilihan ganda yang telah terlebih dahulu diuji Validitas,reliabilitas,tingkat kesukaran, dan daya beda. Hasil penelitian diketahui bahwa hasil belajar model belajar project based learning diperoleh nilai rata-rata siswa pada kelas eksperimen yaitu 77,33 sedangkan kelas kontrol 71,16. Dari hasil perhitungan uji hipotesis diperoleh thitung 3,261 dan ttabel adalah 1,670, maka thitung  > ttabel atau 3,261 > 1,670, sehingga dapat disimpulkan  bahwa hipotesis alternative (Ha) dalam penelitian ini diterima sekaligus menolak hipotesis nihil (Ho) dengan kata lain hasil belajar siswa kelas XI Teknik Instalasi Tenaga Listrik pada kompetensi memahami instalasi dan pengukuran sistem pembumian dengan model belajar project based learning (PJBL) lebih tinggi dari hasil belajar siswa dengan menggunakan model belajar konvensional. Kata Kunci: Model belajar project based learning, hasil belajar